Examining the Trade Effect of Certain Customs and Administrative Procedures - Wilson, Norbert (OECD Publishing, 2007)
Recent research at OECD provides new evidence that customs and administrative procedures have substantial effects on trade flows. Although customs and administrative procedures are necessary for the smooth application of trade and other policies, they can ?thicken? the borders between trading partners if the customs and administrative procedures are more stringent than necessary or...
Keywords: Trade